2004
DOI: 10.1007/s00276-004-0238-y
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and clinical study of the common fibular nerve. Part 1: Anatomical study

Abstract: The aims of this research were: (1) to minimize injury to the common fibular nerve by a detailed anatomical study of the nerve and its branches and (2) clinically to establish a protocol for preoperative and postoperative assessment of patients undergoing surgery on the proximal third of the leg. Thus the incidence of fibular nerve palsy would definitely be negligible. The first part of the research consisted of an anatomical study of the common fibular nerve and its branches, paying particular attention to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 12 publications
1
17
3
1
Order By: Relevance
“…Therefore, MEP of SFN and DFN are clinically important. When comparing the number of MEP of lateral and anterior leg muscles with other studies, our results were quite different (9,11). Number of MEP to FLM was consistent with Lee et al's study; they studied on 43 legs and reported FLM has two MEP (53.8%) predominantly (11) (in our study 56%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, MEP of SFN and DFN are clinically important. When comparing the number of MEP of lateral and anterior leg muscles with other studies, our results were quite different (9,11). Number of MEP to FLM was consistent with Lee et al's study; they studied on 43 legs and reported FLM has two MEP (53.8%) predominantly (11) (in our study 56%).…”
Section: Discussionsupporting
confidence: 86%
“…Iatrogenic nerve damage during osteosynthesis of the proximal tibia or correction osteotomies at the leg are followed by consecutive loss of sensory and "foot drop" syndromes (5). In the lower limb 30% of nerve injuries are to the common fibular nerve (9). Considering the high frequency and morbidity of CFN damage, the localization and the branching pattern of the nerve must be known more clearly.…”
Section: Discussionmentioning
confidence: 99%
“…We identified unusual nerve palsy after FDEO in a patient with common peroneal and reported this unusually high division of DPN. Frequent causes of DPN injury include trauma, fractures, dislocations, neoplasms, ischemic neuropathy, diabetic neuropathy, nerve entrapment, compression, placement of casts, immobilizers, or ring fixators around the leg, proximal tibial osteotomy, biopsy, reconstruction procedures, total knee arthroplasty, and fasciotomy [8][9][10][11][12][13][14][15][16][17]. Up to a 9% neurological complication rate after a FDEO has been reported in the literature [6].…”
Section: Discussionmentioning
confidence: 99%
“…aware of the regional topography of the deep peroneal nerve within the proximal fibular compartment, regarding the distribution of its muscular branches, especially for performing the biopsy of the fibular head (Aigner et al, 2004;Reebye, 2004). To minimize damage to the deep peroneal nerves, the present study was performed to provide the surgeon with an adequate and more precise knowledge of the anatomical relationship between the peroneal nerves and the adjacent anatomical structures around the proximal fibula, with special regard to define the boundaries of a ''safe'' area when performing a biopsy of the fibular head.…”
Section: Discussionmentioning
confidence: 99%